Reformasi Eksekusi Putusan Mahkamah Agung : Mewujudkan Peradilan yang Responsif dan Efisien - Siska Ayu Anggraini (Al Fuadiy Jurnal Hukum Keluarga Islam, 2024)
This study aims to examine the reform of the execution of Supreme Court decisions in order to create a more responsive and efficient judiciary. The background of this research is driven by findings that the execution of Supreme Court decisions in Indonesia still faces various obstacles, both procedural and institutional, leading to delays in the implementation of court decisions. The research method used is a qualitative approach with an in-depth literature review and interviews with legal practitioners. The findings of the study indicate that the main obstacles in the execution of decisions lie in the misalignment between existing regulations and their implementation in practice, complex bureaucracy, and the lack of coordination among related institutions. The implications of this research point to the need for procedural reform, improvement of human resource quality, and the utilization of information technology to enhance the efficiency and transparency of decision execution. This study suggests that public participation in monitoring the execution process could also increase the accountability of the judicial system in Indonesia.